Penerapan Mesin Pemotong Kerupuk Semi Otomatis dan Perbaikan Manajemen untuk Meningkatkan Produktivitas Produsen Kerupuk di Sidoarjo - Sudarso Sudarso; Albrian Fiky Prakoso; Theodorus Wiyanto Wibowo; Yunus Yunus (Jurnal Pengabdian Pada Masyarakat, 2022)
APPLİCATİON OF SEMİ-AUTOMATİC CRACKER CUTTİNG MACHİNE AND MANAGEMENT IMPROVEMENTS TO INCREASE PRODUCTİVİTY OF CRACKER PRODUCERS İN SİDOARJO. This PKM partner is a cracker SME “UD. SETUM JAYA” belongs to M. Faisol Hidayat, whose address is at Tlasih village, Tulangan sub-district, Sidoarjo district. The production capacity of this partner SME is ± 400 kg/day. The purpose of implementing PKM is to help solve priority problems in the production and management aspects of Mitra cracker SMEs. The priority problem in the production aspect is the low productivity of cracker cutting and the problem in the management aspect is production management and financial management that have not been managed properly. The process of cutting crackers in partner SMEs is done manually, the average production capacity is ± 100 crackers / minute, the quality of the products cut is not uniform, some are too thick and some are too thin. To solve the problem of the low priority of the quality and quantity of cracker cutting production, it is done through the application of a semi-automatic cracker cutting machine which has 6 blades mounted on a mechanical rotating disc of an electric motor. This cracker cutting machine has a production capacity of at least 1,376 crackers/minute, so that it can increase the production capacity of cutting crackers by ± 14 times compared to manual cutting of ± 100 pieces/minute. Meanwhile, to solve the problems of production management and financial management of partner cracker SMEs, this is done through training and assistance on how to organize the production environment, production process flow, preparation of raw materials and application of machines for production activities and to solve financial management problems, this is done by recording business financial flows using books. simple cash. The results of the implementation of this PKM program are: (1) a semi-automatic mechanical electric motor cracker cutting machine, and (2) changes in the production management and financial management of partner cracker SMEs that are better according to the training.